Local Tomography in Electron Microscopy. - Quinto, Eric Todd.; Oktem, O. (Tufts University. Tisch Library., 2016)
We present a new local tomographic algorithm applicable to electron microscopetomography. Our algorithm applies to the standard data acquisition method, single-axis tilting, aswell as to more arbitrary acquisition methods including double axis and conical tilt. Using microlocalanalysis we put the reconstructions in a mathematical context, explaining which singularities arestably visible from the limited data given by the data collection protocol in the electron microscope.Finally, we provide reconstructions of real specimens from electron tomography data.